2019
DOI: 10.12659/msm.914029
|View full text |Cite|
|
Sign up to set email alerts
|

Costunolide Inhibits the Growth of OAW42-A Multidrug-Resistant Human Ovarian Cancer Cells by Activating Apoptotic and Autophagic Pathways, Production of Reactive Oxygen Species (ROS), Cleaved Caspase-3 and Cleaved Caspase-9

Abstract: Background Worldwide, ovarian cancer has a high mortality rate due to the difficulty in diagnosing early-stage disease and resistance to chemotherapy agents. Costunolide is a plant-derived sesquiterpene lactone with anti-oxidant properties. This study aimed to investigate the effects of costunolide on cell growth, apoptosis, autophagy, the production of reactive oxygen species (ROS), cleaved caspase-3, and cleaved caspase-9 on the multidrug-resistant ovarian cancer cell line, OAW42-A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Consistent with our hypothesis, pretreatment with the antioxidant NAC substantially inhibited ROS generation and rescued TPL-induced autophagy, as supported by our results revealing that NAC markedly blocked TPL-induced autophagosome/autolysosome formation, LC3 conversion and p62 degradation in SKOV3/DDP cells. These data were consistent with those of previous studies which revealed that costunolide and cinobufagin induced autophagy in cancer cells through ROS production ( 33 , 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our hypothesis, pretreatment with the antioxidant NAC substantially inhibited ROS generation and rescued TPL-induced autophagy, as supported by our results revealing that NAC markedly blocked TPL-induced autophagosome/autolysosome formation, LC3 conversion and p62 degradation in SKOV3/DDP cells. These data were consistent with those of previous studies which revealed that costunolide and cinobufagin induced autophagy in cancer cells through ROS production ( 33 , 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, incubation of multidrug resistant ovarian cancer cells (OAW42-A) with costunolide attenuated cell growth with an IC 50 of 25 µM, and induced apoptosis, which was mediated through induction of Bax, decreased the expression of Bcl-2 and cleavage of caspase-3 and 9. Moreover, the compound induced autophagy as evidenced by the elevated expression of LC3 II and Beclin 1 [65].…”
Section: Therapeutic Potential Of Costunolidementioning
confidence: 99%
“…Cleaved caspase 3 functions as a kind of control tower of apoptosis: it cleaves poly (ADP-ribose) polymerase (PARP), cytokeratin 18, vimentin, actin and other intracytoplasmic proteins. Cleaved caspase 3 has been applied to detecting apoptotic neoplastic cells in paraffin sections [ 24 - 26 ].…”
Section: Discussionmentioning
confidence: 99%